High-thermal-shock insulating brick based on aluminum ash and preparation method of high-thermal-shock insulating brick

By hydrolyzing and calcining the secondary aluminum ash, high-thermal shock insulation bricks were prepared in combination with other raw materials, which solved the problem of aluminum ash utilization and the poor thermal shock stability of JM23 bricks, and achieved low-cost and high-performance thermal insulation brick products.

CN119569430APending Publication Date: 2025-03-07JIN GANG NEW MATERIALS +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411491965.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Among the existing refractory materials, the utilization of aluminum ash is limited by the environmental pollution of its active ingredients and the difficulty in effectively dealing with it. The JM23 lightweight bricks used in ceramic roller kilns have poor thermal shock stability and short service life.

Method used

By hydrolyzing and calcining the secondary aluminum ash, the content of AlN is reduced, and combined with raw materials such as α-alumina, magnesium sand, kaolin and wood chips, high thermal shock insulation bricks with low volume density and high thermal shock stability are prepared.

Benefits of technology

It realizes the effective utilization of aluminum ash resources, reduces the production cost of heat-insulating bricks, improves its thermal shock resistance and thermal conductivity, extends the service life of the kiln, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-thermal-shock heat-insulating brick based on aluminum ash and a preparation method of the high-thermal-shock heat-insulating brick, and relates to the field of refractory materials. The aluminum ash-based high thermal shock insulation brick is mainly prepared from the following raw materials in parts by weight: 40-50 parts of treated aluminum ash, 8-15 parts of alpha-aluminum oxide, 5-10 parts of magnesia and 30-40 parts of kaolin, 50-60 parts of wood chips and 3-5 parts of a binding agent; wherein the sum of the parts by weight of the treated aluminum ash, the alpha-aluminum oxide, the magnesia and the kaolin is 100; the treated aluminum ash is a product obtained after secondary aluminum ash is hydrolyzed and calcined, the content of AlN in the secondary aluminum ash is larger than or equal to 30 wt%, and the content of AlN in the treated aluminum ash is smaller than or equal to 3 wt%. The heat-insulating brick disclosed by the invention is small in volume density, good in thermal shock resistance and low in production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of refractory materials, and in particular to a high thermal shock insulation brick based on aluminum ash and a preparation method thereof. Background Art

[0002] Aluminum ash is the industrial waste slag of aluminum smelting enterprises such as electrolytic aluminum plants, aluminum profile plants, and foundry aluminum alloy plants. It contains some chemical components such as metal aluminum, aluminum oxide, and magnesium oxide, and has potential application value. But at the same time, aluminum ash also contains some AlN, Al4C3, NaF, etc. Among them, metal aluminum particles, AlN, Al4C3 and other substances are highly active, and will produce flammable and toxic gases when in contact with water or in humid air, which are highly environmentally harmful; fluorine-containing compounds and a small amount of heavy metals have leachable toxicity, causing serious pollution to water and air, and also making aluminum ash difficult to use in the future. The commonly used process is to treat aluminum ash by alkali leaching or acid leaching, but after alkali leaching, some metaaluminates are often formed, which are low-melting-point substances, which will cause the pores of porous refractory materials to close prematurely and weaken their refractory properties. The products obtained by acid leaching are mostly flocculent aluminum chloride, which is also difficult to use in refractory materials.

[0003] On the other hand, the preheating zone and cooling zone of the ceramic roller kiln currently use a body density of 0.8g / cm 3 JM23 lightweight brick masonry, the main mineral phase of this product is mullite, but it also contains a certain amount of quartz phase, and the thermal shock stability is average, generally need to be replaced after 3 to 5 years of use. If the thermal insulation bricks with good thermal shock stability and lower body density are used instead of JM23 bricks, the service life of the kiln can be increased, the energy consumption of the kiln can be reduced, the cost can be reduced, and the competitiveness of the enterprise can be enhanced. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a high thermal shock insulation brick based on aluminum ash, which has high thermal shock stability, low bulk density and low cost.

[0005] Another technical problem to be solved by the present invention is to provide a method for preparing high thermal shock insulation bricks.

[0006] In order to solve the above technical problems, the present invention provides a high thermal shock insulation brick based on aluminum ash, which is mainly made of the following raw materials in parts by weight:

[0007] 40-50 parts of processed aluminum ash, 8-15 parts of α-alumina, 5-10 parts of magnesia, 30-40 parts of kaolin, 50-60 parts of sawdust, and 3-5 parts of binder;

[0008] Wherein, the sum of the weight parts of the treated aluminum ash, α-alumina, magnesia and kaolin is 100 parts;

[0009] The treated aluminum ash is a product of hydrolyzing and calcining secondary aluminum ash, wherein the content of AlN in the secondary aluminum ash is ≥30wt%, and the content of AlN in the treated aluminum ash is ≤3wt%.

[0010] As an improvement of the above technical solution, the preparation method of the treated aluminum ash is:

[0011] (1) Mixing secondary aluminum ash and water, treating at 80-100° C. for 3-10 hours, and separating the solid and liquid to obtain an intermediate; wherein the liquid-to-solid ratio is 1:1-5:1;

[0012] (2) calcining the intermediate at 600-1200° C. in an oxygen-containing atmosphere for 0.5-2 h to obtain a processed aluminum ash product.

[0013] As an improvement of the above technical solution, in step (1), the liquid-to-solid ratio is 2:1 to 4:1.

[0014] As an improvement of the above technical solution, in step (2), the calcination temperature is 1000-1200° C., and the calcination time is 1-2 hours.

[0015] As an improvement of the above technical solution, the content of Al2O3 in the treated aluminum ash is 75-90wt%, the content of SiO2 is 1-3wt%, the content of MgO is 5-10wt%, and the content of Fe2O3 is 0.5-2wt%;

[0016] The maximum particle size of the treated aluminum ash is ≤44 μm.

[0017] As an improvement of the above technical solution, the content of Al2O3 in the α-alumina is ≥99.5wt%, and the maximum particle size is ≤3μm;

[0018] The content of MgO in the magnesia is ≥95wt%, the content of CaO is ≤1wt%, and the maximum particle size is ≤74μm.

[0019] The Al2O3 content in the kaolin is ≥35wt%, the Fe2O3 content is ≤1.0wt%, and the maximum particle size is <74μm.

[0020] As an improvement of the above technical solution, the binder is selected from one or more of polypropylene fiber, sodium alginate, and polyvinyl alcohol.

[0021] As an improvement of the above technical solution, the volume density of the high thermal shock insulation brick is 0.35-0.45 g / cm 3 , the compressive strength is 1.0~1.5MPa, and the line change rate of 1300℃×24h re-burning is ±0.2%;

[0022] When the hot surface temperature is 1000°C, the thermal conductivity is 0.18~0.24W / (m·K).

[0023] Correspondingly, the present invention also discloses a method for preparing a high thermal shock insulation brick, which is used to prepare the above-mentioned high thermal shock insulation brick based on aluminum ash, and comprises:

[0024] (1) 40-50 parts of treated aluminum ash, 8-15 parts of α-alumina, 5-10 parts of magnesia, 30-40 parts of kaolin, and 3-5 parts of a binder are mixed uniformly;

[0025] (2) adding 50 to 60 parts of sawdust and a preset amount of water, and mixing them evenly to obtain a slurry; wherein the water content of the slurry is 30 to 40%;

[0026] (3) casting the slurry to obtain a green body;

[0027] (4) The green body is dried and fired to obtain a finished high thermal shock insulation brick.

[0028] As an improvement of the above technical solution, in step (4), the sintering temperature is 1300-1400°C.

[0029] The implementation of the present invention has the following beneficial effects:

[0030] The high thermal shock insulation brick based on aluminum ash of the present invention is mainly prepared from 40-50 parts of processed aluminum ash, 8-15 parts of α-alumina, 5-10 parts of magnesia, 30-40 parts of kaolin, 50-60 parts of sawdust, and 3-5 parts of binder. In the high thermal shock insulation brick obtained based on the formula system, the main crystal phases are alumina phase and magnesium aluminum spinel phase, which effectively improves the thermal shock resistance of the insulation brick and reduces its volume density. In addition, the processed aluminum ash in the present invention is the product of hydrolysis and calcination of secondary aluminum ash, and its AlN content is ≤3wt%, which effectively avoids the adverse effects of AlN on insulation bricks, realizes the resource utilization of aluminum ash, and reduces the production cost of insulation bricks. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below in conjunction with specific implementation methods.

[0032] The present invention provides a high thermal shock insulation brick based on aluminum ash, which is mainly made of the following raw materials in parts by weight:

[0033] 40-50 parts of processed aluminum ash, 8-15 parts of α-alumina, 5-10 parts of magnesia, 30-40 parts of kaolin; 50-60 parts of wood chips, 3-5 parts of binder; wherein the sum of the weight parts of the processed aluminum ash, α-alumina, magnesia and kaolin is 100 parts.

[0034] The treated aluminum ash is the product of hydrolysis and calcination of secondary aluminum ash. The AlN content in the secondary aluminum ash before treatment is ≥30wt%, and the AlN content in the treated aluminum ash after treatment is ≤3wt%. It should be noted that AlN is a harmful component in secondary aluminum ash. It will produce ammonia when it meets water, alkali solution and acid solution, which makes it difficult to apply to the production process of thermal insulation bricks with water slurry. In addition, when AlN is roasted in an oxygen-containing atmosphere, it will also release nitrogen in the range of 600 to 1300°C, which is not conducive to the formation of a uniform porous structure of thermal insulation bricks and reduces their thermal shock resistance. Therefore, in the present invention, the secondary aluminum ash is firstly subjected to hydrolysis and calcination treatment. Based on this treatment, AlN can be basically converted into Al2O3 (AlN residual amount ≤ 3wt%), weakening the adverse effects of AlN; secondly, Al(OH)3 generated during the hydrolysis process can be converted into Al2O3; it is prevented from decomposing and producing water vapor in the later stage of firing, destroying the pore structure of the insulation brick; thirdly, it is prevented from generating too much fusible material, which makes the pores in the insulation brick close prematurely. It should be noted that the content of AlN here refers to the content of AlN phase, which is quantitatively measured by XRD.

[0035] Preferably, in some embodiments, the preparation method for processing aluminum ash comprises the following steps:

[0036] (i) mixing secondary aluminum ash and water, treating at 80-100° C. for 3-10 hours, and obtaining an intermediate after solid-liquid separation;

[0037] Among them, the liquid-to-solid ratio is 1:1 to 5:1. Based on this range, it can effectively promote the conversion of Al element, Al4C3, etc. in secondary aluminum ash into Al(OH)3, and can also increase the ratio of AlN converted into Al(OH)3, and can also effectively remove soluble salts such as NaCl and NaF. Exemplarily, the liquid-to-solid ratio is 1.2:1, 1.5:1, 1.8:1, 2.1:1, 2.4:1, 2.7:1, 3:1, 3.3:1, 3.6:1, 3.9:1, 4.2:1, 4.5:1 or 4.8:1, but not limited to this. Preferably it is 2:1 to 4:1, and more preferably it is 2.5:1 to 4:1. It should be noted that the liquid-to-solid ratio in the present invention refers to the ratio of the volume of water to the weight of secondary aluminum ash, and the corresponding proportional relationship is mL:g or a proportional relationship that expands or reduces the proportional relationship by multiples, but is not limited to this.

[0038] The treatment temperature is 80-100°C, which can promote the conversion of various substances into Al(OH)3. Exemplarily, the treatment temperature is 83°C, 86°C, 89°C, 91°C, 94°C, 97°C or 99°C, but is not limited thereto. Preferably, it is 90-100°C, and more preferably, it is 92-98°C.

[0039] The treatment time is 3 to 10 hours, exemplified by 3.4 hours, 4.2 hours, 5 hours, 5.7 hours, 6.4 hours, 7.2 hours, 8 hours, 8.8 hours, 9.2 hours or 9.8 hours, but not limited thereto, preferably 3 to 5 hours, more preferably 3 to 4 hours.

[0040] Preferably, in some embodiments of the present invention, the secondary aluminum ash is ground and then subjected to hydrolysis treatment. The grinding can break the coating structure existing in the secondary aluminum ash, such as breaking the aluminum oxide coated on the surface of the Al element, so as to improve the hydrolysis efficiency. Specifically, the average particle size of the secondary aluminum ash before grinding is 35 to 60 μm, and the average particle size after grinding is 20 to 40 μm.

[0041] (ii) calcining the intermediate in an oxygen-containing atmosphere to obtain a processed aluminum ash product;

[0042] By calcining in an oxygen-containing atmosphere, AlN and Al(OH)3 can be converted into alumina, and at the same time, the magnesium-aluminum spinel can be activated. It should be noted that the secondary aluminum ash contains a large amount of AlN (≥30wt%), and the activity of AlN is relatively high, and it can react with hot water, but as the reaction progresses, a hydrated aluminum oxide coating will form on the surface of AlN, hindering the hydrolysis reaction. Therefore, the present invention subsequently calcines the treated intermediate in an oxygen-containing atmosphere to promote further decomposition of AlN.

[0043] Specifically, the calcination temperature is 600-1200°C, exemplarily 680°C, 740°C, 800°C, 850°C, 900°C, 960°C, 1030°C, 1090°C or 1140°C, but not limited thereto, preferably 1000-1200°C, more preferably 1000-1100°C.

[0044] Specifically, the calcination time is 0.5 to 2 hours, exemplified by 0.7 hours, 0.9 hours, 1.1 hours, 1.3 hours, 1.5 hours, 1.7 hours or 1.9 hours, but not limited thereto, preferably 1 to 2 hours, more preferably 1.5 to 2 hours.

[0045] Preferably, in some embodiments of the present invention, the intermediate is ground and then calcined, and the coating structure on the surface of the AlN particles can be broken by grinding, thereby improving the calcination efficiency. Specifically, the average particle size of the intermediate material after grinding is 10 to 20 μm, and the maximum particle size is ≤44 μm.

[0046] The content of Al2O3 in the treated aluminum ash obtained based on the above preparation method is 75-90wt%, the content of SiO2 is 1-3wt%, the content of MgO is 5-10wt%, and the content of Fe2O3 is 0.5-2wt%; and the maximum particle size is ≤44μm. This treated aluminum ash is used in large amounts in insulation bricks, which can reduce costs; at the same time, it can also provide abundant Mg and Al sources to improve the various properties of insulation bricks. It should be noted that the content of Al2O3, MgO, and Fe2O3 here refer to the content of chemical components, not the content of physical phases (for example, Al in AlN, Al2O3, and Al(OH)3 is calculated as Al2O3), which can be measured by ICP, XRF, and titration, but is not limited to this. The chemical composition of the other raw materials described below is also measured by the above method.

[0047] Specifically, the amount of aluminum ash used for treatment is 40 to 50 parts, exemplarily 41.5 parts, 42.5 parts, 43 parts, 45 parts, 47 parts, 48 ​​parts or 49 parts, but not limited thereto, preferably 42 to 50 parts, more preferably 45 to 50 parts.

[0048] Specifically, in some embodiments of the present invention, the content of Al2O3 in α-alumina is ≥99.5wt%, and its maximum particle size is ≤3μm. This α-alumina has a low impurity content and can better improve the strength and thermal shock resistance of the insulation brick.

[0049] Specifically, the amount of α-alumina is 8 to 15 parts, exemplarily 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 16 parts, 17.5 parts, 18 parts or 19.5 parts, but not limited thereto, preferably 10 to 15 parts, more preferably 12 to 15 parts.

[0050] Specifically, in some embodiments of the present invention, the content of MgO in the magnesia is ≥95wt%, the content of CaO is ≤1wt%, and the maximum particle size is ≤74μm. The high MgO content in the magnesia can increase the content of cordierite phase in the finished insulation brick and improve its thermal shock resistance. At the same time, its low CaO content avoids premature melting and affects the uniform distribution of pores.

[0051] Specifically, the amount of magnesia is 5 to 10 parts, exemplarily 5.5 parts, 6 parts, 6.5 parts, 8 parts, 8.5 parts, 9 parts or 9.5 parts, but not limited thereto, preferably 5 to 8 parts, more preferably 6 to 8 parts.

[0052] Specifically, in some embodiments of the present invention, the Al2O3 content in kaolin is ≥35wt%, the Fe2O3 content is ≤1.0wt%, and the maximum particle size is <74μm. Kaolin can provide plasticity in the green body stage, which is convenient for molding. During the firing process, it can provide a Si source to form cordierite, and a small amount of mullite will also be formed, which together optimizes the thermal shock resistance.

[0053] Specifically, the amount of kaolin is 30 to 40 parts, exemplarily 31 parts, 33 parts, 35 parts, 37 parts or 39 parts, but not limited thereto, preferably 30 to 38 parts, more preferably 30 to 33 parts.

[0054] Specifically, in some embodiments of the present invention, the average particle size of the sawdust is ≤200 μm, preferably, the average particle size is 50-200 μm. The amount of sawdust used is 50-60 parts.

[0055] Specifically, in some embodiments of the present invention, the binder is selected from one or more of polypropylene fiber, sodium alginate, and polyvinyl alcohol. This binder can optimize the forming properties of the green body, thereby reducing the amount of kaolin used to a certain extent and preventing the quartz phase obtained by the decomposition of residual kaolin in the insulating brick.

[0056] Specifically, the amount of the binder is 3 to 5 parts, exemplarily 3.4 parts, 3.8 parts, 4.2 parts, 4.6 parts or 4.8 parts, but not limited thereto, preferably 4 to 5 parts.

[0057] Accordingly, the present invention also provides a method for preparing a high thermal shock insulation brick, which is used to prepare the above-mentioned high thermal shock insulation brick based on aluminum ash, and is characterized by comprising:

[0058] (1) 40-50 parts of treated aluminum ash, 8-15 parts of α-alumina, 5-10 parts of magnesia, 30-40 parts of kaolin, and 3-5 parts of a binder are mixed uniformly;

[0059] (2) Add 50 to 60 parts of sawdust and a preset amount of water, mix well to obtain a slurry; wherein the moisture content of the slurry is;

[0060] (3) casting the slurry to obtain a green body;

[0061] (4) The green body is dried and fired to obtain a finished high thermal shock insulation brick.

[0062] Specifically, the sintering temperature is 1300-1400°C.

[0063] Specifically, the volume density of the high thermal shock insulation brick prepared based on the above formula and preparation method is 0.35-0.45 g / cm 3The compressive strength is 1.0~1.5MPa, and the line change rate of 1300℃×24h re-firing is ±0.2%; when the hot surface temperature is 1000℃, the thermal conductivity is 0.18~0.24W / (m·K).

[0064] The present invention will be further described below with specific embodiments:

[0065] Example 1

[0066] This embodiment provides a high thermal shock insulation brick based on aluminum ash, and its formula is as follows:

[0067] 50 parts of processed aluminum ash, 8 parts of α-alumina, 5 parts of magnesia, 37 parts of kaolin, 50 parts of sawdust, and 5 parts of admixture;

[0068] The content of Al2O3 in α-alumina is 99.5wt%, and the maximum particle size is 2.5μm; the content of MgO in magnesia is 96wt%, the content of CaO is 0.5wt%, and the maximum particle size is 66μm; the content of Al2O3 in kaolin is 36.5wt%, the content of Fe2O3 is 1.0wt%, and the maximum particle size is 70μm. The average particle size of sawdust is 70μm. The admixture is sodium alginate.

[0069] Wherein, the preparation method of processing aluminum ash is:

[0070] (i) grinding secondary aluminum ash (average particle size of 54.3 μm, AlN content of 33.5 wt%) to an average particle size of 32 μm, then mixing with water, stirring and reacting at 95° C. for 3.5 h; and obtaining an intermediate after solid-liquid separation; wherein the liquid-to-solid ratio is 3:1;

[0071] (ii) The intermediate is ground to an average particle size of 18.3 μm, and then calcined at 1080° C. for 2 h to obtain a finished product of treated aluminum ash.

[0072] Among them, the content of Al2O3 in the treated aluminum ash is 76.3wt%, the content of SiO2 is 1.5wt%, the content of MgO is 6.3wt%, and the content of Fe2O3 is 0.7wt%; its AlN content is 1.3wt%, the average particle size is 19.5μm, and the maximum particle size is 42.8μm.

[0073] The preparation method of high thermal shock insulation brick is:

[0074] (1) Mix the treated aluminum ash, α-alumina, magnesia, kaolin and binder evenly;

[0075] (2) adding sawdust and a preset amount of water, and mixing them evenly to obtain a slurry; wherein the water content of the slurry is 38%;

[0076] (3) casting the slurry to obtain a green body;

[0077] (4) Drying and firing the green body to obtain the finished high thermal shock insulation brick, wherein the firing temperature is 1300°C ± 10°C.

[0078] Example 2

[0079] This embodiment provides a high thermal shock insulation brick based on aluminum ash, and its formula is as follows:

[0080] 48 parts of processed aluminum ash, 10 parts of α-alumina, 7 parts of magnesia, 35 parts of kaolin, 55 parts of sawdust, and 4 parts of admixture;

[0081] The content of Al2O3 in α-alumina is 99.5wt%, and the maximum particle size is 2.5μm; the content of MgO in magnesia is 95.2wt%, the content of CaO is 0.5wt%, and the maximum particle size is 74μm; the content of Al2O3 in kaolin is 36.5wt%, the content of Fe2O3 is 0.85wt%, and the maximum particle size is 72μm. The average particle size of sawdust is 65μm. The additives include: 1 part of polypropylene fiber and 3 parts of sodium alginate.

[0082] Wherein, the preparation method of processing aluminum ash is:

[0083] (i) grinding secondary aluminum ash (average particle size of 54.3 μm, AlN content of 33.5 wt%) to an average particle size of 32 μm, then mixing with water, stirring and reacting at 95° C. for 3.5 h; and obtaining an intermediate after solid-liquid separation; wherein the liquid-to-solid ratio is 3:1;

[0084] (ii) The intermediate is ground to an average particle size of 18.3 μm, and then calcined at 1080° C. for 2 h to obtain a finished product of treated aluminum ash.

[0085] Among them, the content of Al2O3 in the treated aluminum ash is 76.3wt%, the content of SiO2 is 1.5wt%, the content of MgO is 6.3wt%, and the content of Fe2O3 is 0.7wt%; its AlN content is 1.3wt%, the average particle size is 19.5μm, and the maximum particle size is 42.8μm.

[0086] The preparation method of high thermal shock insulation brick is:

[0087] (1) Mix the treated aluminum ash, α-alumina, magnesia, kaolin and binder evenly;

[0088] (2) adding sawdust and a preset amount of water, and mixing them evenly to obtain a slurry; wherein the water content of the slurry is 36%;

[0089] (3) casting the slurry to obtain a green body;

[0090] (4) Drying and firing the green body to obtain the finished high thermal shock insulation brick, wherein the firing temperature is 1320°C ± 10°C.

[0091] Example 3

[0092] This embodiment provides a high thermal shock insulation brick based on aluminum ash, and its formula is as follows:

[0093] 43 parts of processed aluminum ash, 15 parts of α-alumina, 8 parts of magnesia, 34 parts of kaolin, 60 parts of sawdust, and 4 parts of admixture;

[0094] The content of Al2O3 in α-alumina is 99.6wt%, and the maximum particle size is 2.8μm; the content of MgO in magnesia is 96.7wt%, the content of CaO is 0.3wt%, and the maximum particle size is 74μm; the content of Al2O3 in kaolin is 37wt%, the content of Fe2O3 is 0.6wt%, and the maximum particle size is 55μm. The average particle size of sawdust is 70μm. The additives include 1 part of polypropylene fiber, 1 part of sodium alginate, and 2 parts of polyvinyl alcohol.

[0095] Wherein, the preparation method of processing aluminum ash is:

[0096] (i) grinding secondary aluminum ash (average particle size of 54.3 μm, AlN content of 33.5 wt%) to an average particle size of 32 μm, then mixing with water, stirring and reacting at 95° C. for 3.5 h; and obtaining an intermediate after solid-liquid separation; wherein the liquid-to-solid ratio is 3:1;

[0097] (ii) The intermediate is ground to an average particle size of 18.3 μm, and then calcined at 1080° C. for 2 h to obtain a finished product of treated aluminum ash.

[0098] Among them, the content of Al2O3 in the treated aluminum ash is 76.3wt%, the content of SiO2 is 1.5wt%, the content of MgO is 6.3wt%, and the content of Fe2O3 is 0.7wt%; its AlN content is 1.3wt%, the average particle size is 19.5μm, and the maximum particle size is 42.8μm.

[0099] The preparation method of high thermal shock insulation brick is:

[0100] (1) Mix the treated aluminum ash, α-alumina, magnesia, kaolin and binder evenly;

[0101] (2) adding sawdust and a preset amount of water, and mixing them evenly to obtain a slurry; wherein the water content of the slurry is 35%;

[0102] (3) casting the slurry to obtain a green body;

[0103] (4) Drying and firing the green body to obtain the finished high thermal shock insulation brick, wherein the firing temperature is 1350°C ± 10°C.

[0104] Example 4

[0105] This embodiment provides a high thermal shock insulation brick based on aluminum ash, and its formula is as follows:

[0106] 40 parts of processed aluminum ash, 10 parts of α-alumina, 10 parts of magnesia, 40 parts of kaolin, 55 parts of sawdust, and 3 parts of admixture;

[0107] The content of Al2O3 in α-alumina is 99.5wt%, and the maximum particle size is 2.9μm; the content of MgO in magnesia is 96.8wt%, the content of CaO is 0.3wt%, and the maximum particle size is 70μm; the content of Al2O3 in kaolin is 37wt%, the content of Fe2O3 is 0.6wt%, and the maximum particle size is 74μm. The average particle size of sawdust is 72μm. The additives include 1 part of polypropylene fiber and 2 parts of polyvinyl alcohol.

[0108] Wherein, the preparation method of processing aluminum ash is:

[0109] (i) grinding secondary aluminum ash (average particle size of 54.3 μm, AlN content of 33.5 wt%) to an average particle size of 32 μm, then mixing with water, stirring and reacting at 95° C. for 3.5 h; and obtaining an intermediate after solid-liquid separation; wherein the liquid-to-solid ratio is 3:1;

[0110] (ii) The intermediate is ground to an average particle size of 18.3 μm, and then calcined at 1080° C. for 2 h to obtain a finished product of treated aluminum ash.

[0111] Among them, the content of Al2O3 in the treated aluminum ash is 76.3wt%, the content of SiO2 is 1.5wt%, the content of MgO is 6.3wt%, and the content of Fe2O3 is 0.7wt%; its AlN content is 1.3wt%, the average particle size is 19.5μm, and the maximum particle size is 42.8μm.

[0112] The preparation method of high thermal shock insulation brick is:

[0113] (1) Mix the treated aluminum ash, α-alumina, magnesia, kaolin and binder evenly;

[0114] (2) adding sawdust and a preset amount of water, and mixing them evenly to obtain a slurry; wherein the water content of the slurry is 39%;

[0115] (3) casting the slurry to obtain a green body;

[0116] (4) Drying and firing the green body to obtain the finished high thermal shock insulation brick, wherein the firing temperature is 1330°C ± 10°C.

[0117] The high thermal shock insulation bricks of Examples 1 to 4 were tested, and the specific results are shown in the following table:

[0118] Example 1 Example 2 Example 3 Example 4 <![CDATA[Bulk density (g / cm 3 )]]> 0.42 0.35 0.40 0.45 Room temperature compressive strength (MPa) 1.37 1.39 1.43 1.49 1300℃×24h re-burning line change rate (%) -0.02 -0.04 -0.04 -0.03 Thermal conductivity (1000℃, W / (m·K)) 0.19 0.15 0.21 0.24

[0119] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.

Claims

1. A high thermal shock insulation brick based on aluminum ash, characterized in that: It is mainly made of the following raw materials in parts by weight: 40-50 parts of processed aluminum ash, 8-15 parts of α-alumina, 5-10 parts of magnesia, 30-40 parts of kaolin, 50-60 parts of sawdust, and 3-5 parts of binder; Wherein, the sum of the weight parts of the treated aluminum ash, α-alumina, magnesia and kaolin is 100 parts; The treated aluminum ash is a product of hydrolyzing and calcining secondary aluminum ash, wherein the content of AlN in the secondary aluminum ash is ≥30wt%, and the content of AlN in the treated aluminum ash is ≤3wt%.

2. The high thermal shock insulation brick based on aluminum ash according to claim 1, characterized in that: The preparation method of the treated aluminum ash is: (1) Mixing secondary aluminum ash and water, treating at 80-100° C. for 3-10 hours, and separating the solid and liquid to obtain an intermediate; wherein the liquid-to-solid ratio is 1:1-5:1; (2) calcining the intermediate at 600-1200° C. in an oxygen-containing atmosphere for 0.5-2 h to obtain a processed aluminum ash product.

3. The high thermal shock insulation brick based on aluminum ash according to claim 2, characterized in that: In step (1), the liquid-to-solid ratio is 2:1 to 4:

1.

4. The high thermal shock insulation brick based on aluminum ash according to claim 2, characterized in that: In step (2), the calcination temperature is 1000-1200° C. and the calcination time is 1-2 hours.

5. The high thermal shock insulation brick based on aluminum ash according to claim 1, characterized in that: The treated aluminum ash has an Al2O3 content of 75-90wt%, a SiO2 content of 1-3wt%, a MgO content of 5-10wt%, and a Fe2O3 content of 0.5-2wt%; The maximum particle size of the treated aluminum ash is ≤44 μm.

6. The high thermal shock insulation brick based on aluminum ash according to claim 1, characterized in that: The content of Al2O3 in the α-alumina is ≥99.5wt% and the maximum particle size is ≤3μm; The content of MgO in the magnesia is ≥95wt%, the content of CaO is ≤1wt%, and the maximum particle size is ≤74μm. The Al2O3 content in the kaolin is ≥35wt%, the Fe2O3 content is ≤1.0wt%, and the maximum particle size is <74μm.

7. The high thermal shock insulation brick based on aluminum ash according to claim 1, characterized in that: The binder is selected from one or more of polypropylene fiber, sodium alginate and polyvinyl alcohol.

8. The high thermal shock insulation brick based on aluminum ash according to any one of claims 1 to 7, characterized in that: The volume density of the high thermal shock insulation brick is 0.35-0.45 g / cm 3 , compressive strength is 1.0~1.5MPa, The change rate of the re-firing line at 1300℃×24h is ±0.2%; when the hot surface temperature is 1000℃, the thermal conductivity is 0.18~0.24W / (m·K).

9. A method for preparing a high thermal shock insulation brick, used for preparing the high thermal shock insulation brick based on aluminum ash as claimed in any one of claims 1 to 8, characterized in that: include: (1) 40-50 parts of treated aluminum ash, 8-15 parts of α-alumina, 5-10 parts of magnesia, 30-40 parts of kaolin, and 3-5 parts of a binder are mixed uniformly; (2) adding 50 to 60 parts of sawdust and a preset amount of water, and mixing them evenly to obtain a slurry; wherein the water content of the slurry is 25 to 40%; (3) casting the slurry to obtain a green body; (4) The green body is dried and fired to obtain a finished high thermal shock insulation brick.

10. The method for preparing the high thermal shock insulation brick according to claim 9, characterized in that: In step (4), the sintering temperature is 1300-1400°C.

Citation Information

Patent Citations

  • Secondary aluminum ash treatment method with low pollution

    CN109127654A

  • High-efficiency clean resource utilization method for quadratic aluminum dust

    CN109179464A

  • Method for preparing lightweight high-aluminum heat-insulating brick by utilizing aluminum ash

    CN109678556A

  • Method for preparing porous mullite brick from secondary aluminum ash

    CN113173802A

  • Low-cost, high-thermal-shock-resistance, low-thermal-conductivity and light-weight heat-insulating brick and preparation method thereof

    CN114349472A